Internationalization and dissemination of rural territorial development public policies:: model hypotheses for Latin America - Massardier, Gilles; Sabourin, Eric (Sustainability in Debate, 2013)
This article proposes a theoretical and methodological reflexion to analyse the recent and almost simultaneous expansion of national Rural Territorial Development policies in Latin America. The paper therefore puts forward three main hypotheses: The first is that of the existence of Latin American macro-regional models for these public policies. The second is that of the overlapping of three internationalization processes for these policies: inter/transnational circulation of norms, especially via international organizations and arenas; policy transfers; a regionalization process “by below”. The third hypothesis considers an atypical regionalization of this continent which is undergoing a process of internationalized sectoral public policy dissemination. The general purpose of the paper is therefore to understand the types of overlapping existing between these internationalization processes and the ways Rural Territorial Development policies are nationally, regionally and territorially adapted in Latin America.